Perceived Audio Quality for Streaming Stereo Music. - Harte, Naomi; Kokaram, Anil; Hines, Andrew; Gillen, Eoin; Kelly, Damien; Skoglund, Jan (My University, 2014)
Users of audio-visual streaming services expect an ever increasing quality of experience. Channel bandwidth remains a bottleneck commonly addressed with lossy compression schemes for both the video and audio streams. Anecdotal evidence suggests a strongly perceived link between bit rate and quality. This paper presents three audio quality listening experiments using the ITU MUSHRA methodology to assess a number of audio codecs typically used by streaming services. They were assessed for a range of bit rates using three presentation modes: consumer and studio quality headphones and loudspeakers. Our results indicate that with consumer quality headphones, listeners were not differentiating between codecs with bit rates greater than 48 kb/s (p>=0.228). For studio quality headphones and loudspeakers aac-lc at 128 kb/s and higher was differentiated over other codecs (p<=0.001). The results provide insights into quality of experience that will guide future development of objective audio quality metrics.
ACM Multimedia
Keywords: Audio quality; Audio-visual streaming; MUSHRA; YouTube; Audio codec; Digital Engagement; Telecommunications; Signal processing